Pola air tersedia pada beberapa media tanam untuk tanaman strawberry (Fragaria Virginiana) - I Made Dwi Dharma Setiawan; Sumiyati Sumiyati; I Made Nada (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2017)
This study aims to determine water patterns available in different growing media. The study consisted of four treatments namely P1: rice husk charcoal media, P2: cocopeat and compost mix media with 2: 1 ratio, P3: soil and compost mix with 2: 1 ratio and P4: soil media. Field capacity for the entire treatment P1, P2, P3 and P4 from week 2 to week 12 in a row was 77,21% to 80,00%, 50,22% to 52,56%, 42,83% to 44,24%, and 36,70% to 37,95%. Temporary wilting point for all treatments P1, P2, P3 and P4 from week 2 to week 12 in a row was 36,59% to 18,99%, 29,09% and 10,63%, 10, 83% to 5,27% and 10,62% to 6,50%. Available water for strawberry plants for all treatments P1, P2, P3 and P4 from week 2 to week 12 in a row was 7,90 cm to 10,93 cm, 4,27 cm to 7,13 cm, 5,90 cm to 6,84 cm and 4,84 cm to 5,44 cm.